Two new species of Borboropora Kraatz from Mexico (Coleoptera: Staphylinidae: Aleocharinae) - Delgado, Leonardo; Santiago-Jiménez, Quiyari J. (Zootaxa, 2009)
Borboropora pseudoquadriceps Delgado & Santiago-Jiménez, sp. nov., and B. mixe Delgado & Santiago-Jiménez, sp. nov., are described and illustrated. Both species represent the first record of the genus from Mexico. Diagnostic characters of this genus are discussed. A key to the New World species of this genus is also included.